INSTITUTE OF HISTOLOGY AND EMBRYOLOGY IN THE MOST MODERN BUILDING OF MEDICAL FACULTY IN BELGRADE BETWEEN TWO WORLDS WEARS: Institut za histologiju i embriologiju u najmodernijoj zgradi Medicinskog fakulteta u Beogradu između dva svetska rata - Puskas, Nela (Medical Research, 2023)
The Institute of Histology and Embryology was founded in 1921, but moved into its own building a few years later, in 1927. The project of the building was done by the architect Svetozar Jovanović, and the pedimental sculpture was done by the academic sculptor Živojin Lukić. The building housed two institutes: the Institute of Physiology and the Institute of Histology. Each of the institutes had one wing, and both shared the central part of the building, which housed the amphitheater. The building was equipped with the most modern technical devices and provided excellent conditions for scientific work and teaching. In addition, within the Institute of Histology, the Photography Department, the Terminology Department, the central catalog of the books of the Faculty of Medicine were organized, and a museum was also planned. The largest part of the building was destroyed in the German bombing on April 6, 1941. After liberation, according to the project of architect Milan Sekulić, the reconstruction of the central part and the construction of new wings of the building were carried out. Keywords: Faculty of Medicine in Belgrade, Institute of Histology and Embryology, Aleksandar Đ. Kostić